Pengaruh Perencanaan Anggaran dan Pengendalian Intern terhadap Akuntabilitas Keuangan dengan Realisasi Anggaran sebagai Variabel Pemediasi - Musyarofah, Musyarofah; Indarti, M. G. Kentris (Universitas Proklamasi 45, 2024)
The research aims to determine how budget planning and internal control influence budget realization at the UPT of the Central Java Provincial Health Service. To find out how budget planning, budget control, and realization influence regional financial accountability at the UPT of the Central Java Provincial Health Service. The population in this study was 300 UPT of Central Java Provincial Health Service employees. The sampling method uses purposive sampling, i.e. taking samples by determining the criteria first. These criteria are employees who are involved in budget planning and internal control/auditing and have become civil servants. Determining the sample size using the Slovin formula obtained 171 respondents. The data collection method uses a questionnaire. Data analysis uses linear regression analysis. Based on the research results, it can be concluded that budget planning and internal control influence the realization of the Central Java Provincial Health Service UPT budget. Budget planning, internal control, and budget realization influence the financial accountability of the UPT of Central Java Provincial Health Service. Budget realization mediates the influence between budget planning and internal control on the financial accountability of the UPT of Central Java Provincial Health Service.